PRÁTICAS DE APRENDIZAGEM ORGANIZACIONAL: Estudo de casos múltiplos em empresas de consultoria na cidade de São Paulo - Miyazaki, Fernando Rejani (2017)
Organizational learning studies aim to describe and analyze forms and reasons of knowledge creation, development and using in companies, and how these processes help an organization to generate value and competitiveness in their markets. Emphasis was given to organizational learning practices in order to determine initiatives made by companies to generate an learning favorable ambience, while knowledge management practices acts to support and complement organizational learning practices, since they’re related to activities developed in consulting companies, who were focus of this study and composed the cases here described. Discussion contained in this dissertation taken as basis an qualitative and interview-based approach, using content analysis and document analysis, with two cases analyzed individually and in a cross-sectional way, and was conducted between November 2016 and January 2017 in two big consulting companies, based in São Paulo city. When comparing perceptions and statements to the companies’ public documents and to literature-based references, it concludes that the identified practices aim to give workers a set of capabilities suited to their acting in organizations, using previous experiences, best practices mapping and knowledge transferring. Clients’ diversity of profiles and acting areas demand from studied organizations a workforce who simultaneously shows certain quality standards and singularities that gives advantages to these consulting companies and, consequently, to their clients.